As autarquias corporativas e a liberdade de profissão - Mogioni, Cristina Aparecida Faceira Medina (2023)
The present study adresses the issue of freedom of profession as established in the 1988 Federal Constitution’s 5th article, section XIII, which states: “it is free the exercise of any work, craft or profession, if met the professional qualifications established by law”. Inserted within the classical fundamental rights, the freedom of profession has been guaranteed by all the National Constitutions, in a similar way to what today is established by the current Constitution, and which is according to the international juridical order, including the international sphere of human rights. The freedom of profession is a right of macroeconomic importance because it is where the corporate activity has its foundation while an individual right. Embracing the freedom of choice and exercise, and distinguishing profession from work and craft, because it is destined to describe the activity from the professional who possesses specialized and formal competence, ordinarily acquired by University education, as it is the case for doctors, lawyers, engineers, lastly, with intellectual professionals, the freedom of profession established in the Magna Carta is not stark, being subject to the professional qualifications that the law, which is a competence of the Union (art.22, XVI, from the Federal Constitution), comes to establish. The intervention in the freedom of profession is only legitimate upon law that delineates how the restriction is going to be held (formal criterium), which substantially only justifies itself according to public interest reasons, thus demanding adequacy and proportionality between aimed means and ends (material criterium), in order to inhibit that the fondamental right’s essential nucleus is compromised. The self-government of professions, also known as profession police, a true longing of the liberal professionals, has been exercised by the professional councils or corporate autarchies created by law with a juridical personality of public law, bearing in mind the exercise of “typical State activity, which covers even the power of policing, tributing and punishing, in what concerns the exercise of regulated professional activities” (ADI 1717/2002). The professional councils’ public law personality, however, does not produce the total incidence of a public law juridical regime to those entities, but a hybrid juridical regime, which is analyzed in its main aspects, finally by the absence of integration of the councils in the state structure and the control or tutelage of the federal government, by the free choice of its leaders, by the tributal nature of the charged annuities, by the non subjection to the payment regime, by the submission to the fiscalisation of the Union Court of Auditors, by the enjoyment of tributal immunity, by the submission to the rule of public tender for hiring its people, under the CLT regime. It is analyzed in this study the situation of the Brazilian Order of Lawyers (OAB), emphasizing on the interpretation of the Federal Supreme Court, in the ADI 3026/2006, which granted it the juridical nature of an independent public service, without, however, it being considered a corporate autarchy, distinguishing itself from other professional councils. Comparing the OAB with the other corporate autarchies, it concludes that there is no justification to the distinction made to it.